2013
DOI: 10.1080/14786419.2012.665913
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase inhibitor and radical scavenger fractions and isolated compounds from aerial parts ofPeucedanum knappiiBornm

Abstract: In this study, we investigated tyrosinase inhibitory and radical scavenger activities of the hydroalcoholic extract from Peucedanum knappii Bornm aerial parts, together with its fractions. The EtOAc fraction showed the highest antioxidant and anti-tyrosinase activity was selected for the isolation and identification of major active compound(s). Two flavonol glycosides, named rhamnetin-3-O-β-D-glucopyranoside (1) and isorhamnetin-3-O-β-D-glucopyranoside (2) were isolated from the EtOAc fraction. Compound 1 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…All extracts were kept at −20 °C prior to experimental. The total phenolic content, total amino acid content, antioxidant and anti-tyrosinase activity of all samples were performed respectively, following method: Folin-Ciocalteu׳s phenol reagent was used according to the method as previously described [1] . Briefly, the samples solution was incubated at room temperature with Folin and sodium carbonate for 60 minutes.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All extracts were kept at −20 °C prior to experimental. The total phenolic content, total amino acid content, antioxidant and anti-tyrosinase activity of all samples were performed respectively, following method: Folin-Ciocalteu׳s phenol reagent was used according to the method as previously described [1] . Briefly, the samples solution was incubated at room temperature with Folin and sodium carbonate for 60 minutes.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The results were expressed as milligrams of Alanine (Ala) equivalents per 100 g of the each sample (mg Ala/100 g sample weight). DPPH (1, 1-diphenyl-2-picrylhydrazyl radical) radicals reagent was used for evaluated the power of the free radical scavenging capacity of samples [1] . Briefly, samples solution with different concentrations was mixed with methanol solution of DPPH (100 µM).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Arbutin, a structural analog of hydroquinone, can be metabolized into hydroquinone (Blaut et al, 2006), increasing the possibility of getting cancer. Thus, much research has identified tyrosinase inhibitors synthesized in the laboratory (Kubo et al, 2000;Shiino et al, 2001;Jun et al, 2007;Jirawattanapong et al, 2009;Delogu et al, 2010;Yi et al, 2010;Cha et al, 2011;Tajima et al, 2011;Song et al, 2012;Hamidian, 2013;Hamidian et al, 2013;Zhu et al, 2013) and extracted from plants (Piao et al, 2009;Sung et al, 2009;Chang et al, 2011;Liang et al, 2012;Zheng et al, 2012;Sarkhail et al, 2013). Some attention has been drawn to applying peptide sequences for tyrosinase inhibition; however, most of them are fragments isolated from known proteins and peptide-derived compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Total flavonoids content of the extract was estimated as the aluminum chloride colorimetric method by 96-well plate (16). Twenty µL of the extract was mixed with water (80 µL) followed by the addition of NaNO 2 (15%, 6 µL).…”
Section: Determination Of Total Flavonoid Contentmentioning
confidence: 99%
“…Tyrosinase inhibitory activity was carried out according to the procedure as explained by Sarkhail et al (14,16) …”
Section: Determination Of Mushroom Tyrosinase Inhibitory Activitymentioning
confidence: 99%